NLGP Attenuates Murine Melanoma and Carcinoma Metastasis by Modulating Cytotoxic CD8+ T Cells - Bhuniya, Avishek; Guha, Ipsita; Ganguly, Nilanjan; Saha, Akata; Dasgupta, Shayani; Nandi, Partha; Das, Arnab; Ghosh, Sarbari; Ghosh, Tithi; Haque, Enamul; Banerjee, Saptak; Bose, Anamika; et al. (Frontiers in Oncology, 2020)
Neem leaf glycoprotein (NLGP), a natural immunomodulator, attenuates murine carcinoma and melanoma metastasis, independent of primary tumor growth and alterations in basic cellular properties (cell proliferation, cytokine secretion, etc.). Colonization event of invasion–metastasis cascade was primarily inhibited by NLGP, with no effect on metastasis-related invasion, migration, and extravasation. High infiltration of interferon γ (IFN-γ)–secreting cytotoxic CD8+ T cells [CD44+, CD69+, GranB+, IFN-γ+, and interleukin 2+] was documented in the metastatic site of NLGP-treated mice. Systemic CD8+ T cell depletion abolished NLGP-mediated metastasis inhibition and reappeared upon adoptive transfer of NLGP-activated CD8+ T cells. Interferon γ-secreting from CD8+ T cells inhibit the expression of angiogenesis regulatory vascular endothelial growth factor and transforming growth factor β and have an impact on the prevention of colonization. Neem leaf glycoprotein modulates dendritic cells (DCs) for proper antigen presentation by its DC surface binding and upregulation of MHC-I/II, CD86, and CCR7. Neem leaf glycoprotein–treated DCs specifically imprint CXCR3 and CCR4 homing receptors on activated CD8+ T cells, which helps to infiltrate into metastatic sites to restrain colonization. Such NLGP's effect on DCs is translation dependent and transcription independent. Studies using ovalbumin, OVA257−264, and crude B16F10 antigen indicate MHC-I upregulation depends on the quantity of proteasome degradable peptide and only stimulates CD8+ T cells in the presence of antigen. Overall data suggest NLGP inhibits metastasis, in conjunction with tumor growth restriction, and thus might appear as a promising next-generation cancer immunotherapeutic.